Solving unit commitment problem with wind power energy using multi agent evolutionary programming optimization technique / Mohd Ikhwan Mahasan - Mahasan, Mohd Ikhwan (2013)
This thesis presents an approach to search for an optimal solution for Unit Commitment Problem with wind power generation. The objectives of this research are to find the optimal cost of generation and to review the effect of the presence of renewable energy which is the wind energy in the conventional Unit Commitment problem. Unit commitment involves the scheduling of start-up and shutdown of generating units, an indirect determines the optimum power should be generated by each unit committed over a period of time to meet the required load demand at minimum possible cost. In this study, Multi Agent Evolutionary Programming has been used to solve the optimal unit commitment for 24 hour periods. Multi Agent Evolutionary Programming is a combination of two Artificial Intelligent techniques which are Multi Agent System and Evolutionary Programming.